Dosimetric feasibility analysis and presentation of an isotoxic dose-escalated radiation therapy concept for glioblastoma used in the PRIDE trial (NOA-28; ARO-2022-12) - Bodensohn, Raphael; Fleischmann, Daniel F.; Maier, Sebastian H.; Anagnostatou, Vasiliki; Garny, Sylvia; Nitschmann, Alexander; Büttner, Marcel; Mücke, Johannes; Schönecker, Stephan; Unger, Kristian; Hoffmann, Elgin; Paulsen, Frank; et al. (Clinical and Translational Radiation Oncology, 2024)
Background and purpose: The PRIDE trial (NOA-28; ARO-2022-12; NCT05871021) is scheduled to start recruitment in October 2023. Its primary objective is to enhance median overall survival (OS), compared to historical median OS rates, in patients with methylguanine methlyltransferase (MGMT) promotor unmethylated glioblastoma by incorporating isotoxic dose escalation to 75 Gy in 30 fractions. To achieve isotoxicity and counteract the elevated risk of radiation necrosis (RN) associated with dose-escalated regimens, the addition of protective concurrent bevacizumab (BEV) serves as an innovative approach. The current study aims to assess the dosimetric feasibility of the proposed concept. Materials and methods: A total of ten patients diagnosed with glioblastoma were included in this dosimetric analysis. Delineation of target volumes for the reference plans adhered to the ESTRO-EANO 2023 guideline. The experimental plans included an additional volume for the integrated boost. Additionally, the 60 Gy-volume was reduced by using a margin of 1.0 cm instead of 1.5 cm. To assess the risk of symptomatic RN, the Normal Tissue Complication Probability (NTCP) was calculated and compared between the reference and experimental plans. Results: Median NTCP of the reference plan (NTCPref) and of the experimental plan (NTCPex) were 0.24 (range 0.11–0.29) and 0.42 (range 0.18–0.54), respectively. NTCPex was a median of 1.77 (range 1.60–1.99) times as high as the NTXPref. In a logarithmic comparison, the risk of RN is enhanced by a factor of median 2.00 (range 1.66–2.35). The defined constraints for the organs at risk were feasible. Conclusion: When considering the potential protective effect of BEV, which we hypothesized might reduce the risk of RN by approximately two-fold, achieving isotoxicity with the proposed dose-escalated experimental plan for the PRIDE trial seems feasible.
CRIS-Team Scopus Importer:2025-10-13
Keywords: Bevacizumab; Dose escalation; FET PET; Glioblastoma; NTCP; Radiation necrosis